2021
DOI: 10.33774/chemrxiv-2021-qvhml
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DockStream: A Docking Wrapper to Enhance De Novo Molecular Design

Abstract: Recently, we have released the de novo design platform REINVENT in version 2.0. This improved and extended iteration supports far more features and scoring function components, which allows bespoke and tailor-made protocols to maximize impact in small molecule drug discovery projects. A major obstacle of generative models is producing active compounds, in which predictive (QSAR) models have been applied to enrich target activity. However, QSAR models are inherently limited by their applicability domains. To ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…37 Ligand preparation and docking was performed using DockStream, which is integrated with REINVENT, facilitating parallelization over numerous CPU cores. 38 3D coordinates for all agent sampled compounds from the baseline RL and CL experiments were generated using LigPrep. Default parameters were used except for the pH tolerance range set to 7.0 ± 1.0 with Epik and a maximum of two stereoisomers kept per compound.…”
Section: Methodsmentioning
confidence: 99%
“…37 Ligand preparation and docking was performed using DockStream, which is integrated with REINVENT, facilitating parallelization over numerous CPU cores. 38 3D coordinates for all agent sampled compounds from the baseline RL and CL experiments were generated using LigPrep. Default parameters were used except for the pH tolerance range set to 7.0 ± 1.0 with Epik and a maximum of two stereoisomers kept per compound.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to virtual screening, attempts have been made to generate molecules by directly optimizing a docking score [ 19 , 20 , 21 , 22 ]. Recently, Boitreaud et al [ 23 ] suggested the OptiMol approach based on binding energy optimization for drug design using a generative model and docking using adaptive sampling (CbAS) [ 24 ] to maximize the objective function.…”
Section: Introductionmentioning
confidence: 99%